Pengaruh Pendidikan, Pelatihan Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan (Pada Pt. Inti Sukses Garmindo,Semarang) - Aulia, Septin Ambar; , Imron Rosyadi, S.E, M.Si (2016)
The purpose of this study was to determine the effect of education, training and motivation to work productivity of employees at PT. Successful core Garmindo, Semarang. This research was conducted using primary data. The population in this study as many as 2,000 people working at PT. Successful core Garmindo, Semarang. By taking a sample of 100 people using purposive sampling technique. Data analysis method used is the classic assumption test, multiple linear regression, goodnes of fit, and the t test. Results of this study prove that partially education level (X1), training (X2) and motivation (X3) together have a significant impact on employee productivity (Y). Later analysis of the coefficient of determination (Adjusted R Square) education level variable (X1), training (X2) and motivation (X3) impact of 58.1% on the variable employee productivity (Y), while the remaining 41.9% is explained by other variables outside the model. Keywords: Education, Training, Work Motivation, Employee Productivity